Restorative Justice In Indonesian Criminal Code: Navigating Fragmentation And Lessons From Malaysia And The United States - Akbar, Abiandri Fikri (Pandecta Research Law Journal, 2025)
Restorative justice is an approach to criminal case resolution that prioritizes restoration over retribution by involving victims, offenders, their families, and other relevant parties in a participatory process. This study examines the development of restorative justice in Indonesia, particularly its incorporation into the new Indonesian Criminal Code, using a normative legal method combined with a comparative study of practices in the United States and Malaysia. The novelty of this research lies in its focus on Indonesia’s unique regulatory challenges, specifically the persistence of regulatory dissonance due to fragmented implementing regulations and inconsistent law enforcement practices, and in offering a comparative perspective on how harmonized policies in other jurisdictions can provide solutions. The findings reveal that, although the new Code formally accommodates restorative justice principles, the lack of harmonization has resulted in unclear guidelines, varied field applications, and suboptimal victim recovery. Victims often experience confusion in accessing restorative mechanisms, while law enforcement officers face obstacles due to inadequate training and the absence of unified standards. To address these challenges, this paper recommends policy harmonization at all governmental levels, the establishment of coordinated guidelines across law enforcement agencies, and the enhancement of institutional capacity through specialized training. By drawing lessons from the cohesive frameworks adopted in the United States and Malaysia, this study contributes to the existing literature by highlighting the importance of harmonized policies to ensure legal certainty, consistency, and better restorative justice outcomes for both victims and offenders in Indonesia.